1997
DOI: 10.1577/1548-8675(1997)017<0032:leoasb>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Artificial Swim Bladder Deflation in Largemouth Bass: Potential Benefits for Catch-and-Release Fisheries

Abstract: Artificial swim bladder deflation was examined as a technique to increase postrelease survival of largemouth bass Micropterus saltnoides caught from deep water. Depressurizalion was simulated with a hyperbaric chamber. Largemouth bass showed clinical depressurization signs when depressurized from a simulated depth of 3.5 m and were unable to immediately submerge when depressurized from 8.4 m. When depressurized from a simulated depth of 10.5 m. largemouth bass experienced 07c mortality when subsequently held a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 5 publications
7
32
0
Order By: Relevance
“…Similar to past studies on gas bladder deflation, we found no mortality in fish with barotrauma that were subjected to fizzing (e.g., Bruesewitz et al, 1993;Shasteen and Sheehan, 1997). Other studies recorded mortality but found no significant difference between deflated fish and non-deflated fish (e.g., Lee, 1992;Gitschlag and Renaud, 1994), and some studies have shown a positive effect of artificial swim bladder deflation on yellow perch (Keniry et al, 1996), black sea bass and vermillion snapper (Collins et al, 1999).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to past studies on gas bladder deflation, we found no mortality in fish with barotrauma that were subjected to fizzing (e.g., Bruesewitz et al, 1993;Shasteen and Sheehan, 1997). Other studies recorded mortality but found no significant difference between deflated fish and non-deflated fish (e.g., Lee, 1992;Gitschlag and Renaud, 1994), and some studies have shown a positive effect of artificial swim bladder deflation on yellow perch (Keniry et al, 1996), black sea bass and vermillion snapper (Collins et al, 1999).…”
Section: Resultssupporting
confidence: 88%
“…At present, there is apprehension about fizzing because of the potential to inadvertently puncture vital organs and introduce pathogens. In addition, it is unknown whether the fizzed fish are behaviourally compromised and may be unable to swim effectively to avoid predators or forage for food (Shasteen and Sheehan, 1997). Most studies to date on fizzing have been completed in laboratories (e.g., Keniry et al, 1996;Shasteen and Sheehan, 1997), or using mark recapture methods (e.g., Lee, 1992;Bruesewitz et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although, no immediate negative consequences of barotrauma were observed, Hall et al (2009) highlighted the probability of at least some longer-term mortalities, which is also supported by the results of previous studies with other species (Feathers & Knable, 1983;Keniry et al, 1996;Gravel & Cooke, 2008). Venting could be an appropriate mitigation strategy, although there is debate over the effectiveness of this approach, mainly due to considerable species-specific variation in responses (Keniry et al, 1996;Shasteen & Sheehan, 1997;Collins et al, 1999). Further work is required to assess the benefits or otherwise of this procedure for Australian bass.…”
Section: Discussionsupporting
confidence: 60%
“…Environ Manage (2007) 39:760-773 765 Several studies have examined the impact of decompression in fish (Gotshall 1964;Feathers and Knable 1983;Lee 1992;Keniry et al 1996;Shasteen and Sheehan 1997). Most of these have focused on initial or delayed mortality after decompression in largemouth bass (Micropterus salmoides).…”
Section: Raising Fish Slowly From Depthmentioning
confidence: 99%